2002
DOI: 10.1016/s0886-3350(02)01224-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of glistening formation among hydrophobic acrylic intraocular lenses

Abstract: Glistening quantity varied among hydrophobic acrylic IOLs and was temperature dependent. Sensar IOLs were more stable than the 2 other IOL types. The glistening phenomenon must be studied further to eliminate the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 9 publications
3
42
0
2
Order By: Relevance
“…3 Gregori et al 4 showed that glistenings were induced by temperature changes that led to condensation of excessive water in the microvoids of the bulk material on cooling. Tognetto et al 5 found that this opacification happens because Q 2012 ASCRS and ESCRS Published by Elsevier Inc.…”
Section: Resultsmentioning
confidence: 99%
“…3 Gregori et al 4 showed that glistenings were induced by temperature changes that led to condensation of excessive water in the microvoids of the bulk material on cooling. Tognetto et al 5 found that this opacification happens because Q 2012 ASCRS and ESCRS Published by Elsevier Inc.…”
Section: Resultsmentioning
confidence: 99%
“…3,[5][6][7][11][12][13][14]16 Specifically, glistenings in Acrysof IOLs have been shown to be temperature dependent, to be consistent with fluid formation within the acrylic optic, and in some cases, to be related to the packaging system. [2][3][4][5][6][7] However, the potential effect on glistening formation of incorporating a yellow chromophore into the Acrysof material is still unknown. As previously stated, in 2009 our group studied the incidence of glistenings in a large series of eyes with different types of Acrysof IOLs, including eyes with blue light-filtering IOLs (Acrysof SN material).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Glistenings are reported to occur in 57% of patients between 2 months and 16 months after surgery, 5 and the rate is dependent on the type of IOL. 4,[8][9][10] Although several studies [5][6][7]10 have reported whitening on AcrySof hydrophobic acrylic IOLs (Alcon, Inc.), few studies have looked at whether the phenomenon occurs with IOLs of other manufacturers. Furthermore, few studies have assessed impaired transparency of IOL optics based on a precise distinction between glistenings and whitening.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the increase in the intensity of light scattering over time may indicate that the increase was caused by postoperative changes, such as the presence of and increase in the number of factors that result in light scattering in the eye. For IOL Z intraocular lens *Significantly larger than in the middle (P!.05) † Significantly larger than at 1 week (P!.05) instance, glistenings, which are reported to develop postoperatively over time in the optic of some hydrophobic acrylic IOLs, 4,8,9 are caused by light reflected by the boundary of phase separation between supersaturated water and the IOL optic material. 10,12 Whitening makes the surface of the hydrophobic acrylic IOL appear as a white opacity, [5][6][7] and it is difficult to distinguish from glistenings.…”
Section: Discussionmentioning
confidence: 99%